Organization of training students with disabilities in the conditions of comprehensive school - T V Volosovets; E N Kutepova (Peoples' Friendship University of Russia (RUDN University), 2014)
The work presents one of the priority directions of the development of the education system for students with disabilities, namely, the organization of their training in comprehensive educational institutions. The integrated co-teaching is recognized by the world community as the most humane therefore it has become one of the major directions in the Russian educational policy. Today, the task of the state and society is to make sure that all children can get an education and live as fully as possible, regardless of their health problems.